Legal Force of Auction Minutes Through a Case Study at KPKNL Tebing Tinggi - Pardo Sitanggang; Ahmad Ahmad; Agus Darmawan (Universitas Muhammadiyah Tangerang, 2024)
This study aims to analyze the legal force of the Auction Minutes issued by the Office of State Assets and Auction Services, using a case study on Auction Deed No. 245/05/2022 KPKNL Pematang Siantar. It employs a normative legal research method with both case and statutory approaches, combining the analysis of the auction document as primary data with the legal norms of auction law under the Vendu Reglement, Civil Code, and Minister of Finance Regulations as secondary data. The findings show that BAL serves as an authentic deed possessing full evidentiary strength, thereby providing legal protection and certainty for auction winners in acquiring ownership rights over auctioned objects. The study also found several factors that can hinder enforcement of collateral auctions, such as legal objections, procedural defects, administrative land issues, physical control by the executed party, and inconsistencies in legal documentation. Overall, the research concludes that the effectiveness of BAL as an instrument of legal certainty depends heavily on procedural compliance and post-auction administrative and dispute resolution processes. Consequently, BAL plays a crucial role in legitimizing the transfer of rights through the state auction mechanism.